Research Trends On Reading The Yellow Book Using The Al-Miftah Lil Ulum Method : A Bibliometric Study - M. Rifqi Almahmudi; Abdur Rofik (JURNAL ISLAM NUSANTARA, 2025)
The yellow book learning method has a fundamental role in the Islamic boarding school education system in Indonesia because it is the main means of mastering the treasures of classical Islamic science. One of the methods that is famously used is the Al-Miftah Lil Ulum Method from Sidogiri Islamic boadhing school, which is present as a learning innovation that offers a systematic approach in improving the ability to read classical Arabic texts without harakat. This study aims to analyze the development of scientific studies related to the Al-Miftah Lil Ulum Method using a bibliometric analysis approach. Data were collected from Google Scholar and Garuda databases through the keywords "Al-Miftah Lil Ulum Method", "yellow book", "Sidogiri Islamic boarding school", and "yellow book reading method" in the 2012–2025 publication year. The analysis was conducted with the help of Publish or Perish and VOSviewer software to examine publication trends, citation rates, author collaboration, and keyword linkage mapping. The results of the analysis show a significant increase in the number of publications since 2018, with the peak of research occurring in the 2021–2023 period. The dominant themes include the implementation of the Al-Miftah Lil Ulum Method in Islamic boarding schools, its influence on students' ability to read the yellow book, and Islamic boarding school learning innovations. These findings confirm that the Al-Miftah Lil Ulum Method has developed from a local practice to a focus of national academic studies that is relevant to the development of Islamic educational pedagogy in Indonesia.